The Importance of Dose Escalation in the Treatment of Pulmonary Arterial Hypertension with Treprostinil - Piotr Kędzierski; Marta Banaszkiewicz; Michał Florczyk; Michał Piłka; Rafał Mańczak; Maria Wieteska-Miłek; Piotr Szwed; Krzysztof Kasperowicz; Katarzyna Wrona; Szymon Darocha; Adam Torbicki; Marcin Kurzyna (Biomedicines)
Background: Treprostinil, which is administered via continuous subcutaneous or intravenous infusion, is a medication applied in the treatment of pulmonary arterial hypertension (PAH). The dose of treprostinil is adjusted on an individual basis for each patient. A number of factors determine how well patients respond to treatment. Objectives: The aim of this study was to identify factors that may influence the clinical response to the dose of treprostinil at 3 months after the start of therapy. Methods: The factors influencing treatment response were analyzed in consecutive PAH patients who started receiving treprostinil treatment. The treatment efficacy was assessed as improvement in 6 min walk distance (6MWD) and WHO functional class (WHO FC), a reduction in N-terminal prohormone of brain natriuretic peptide (NTproBNP), and the percentage of patients achieving low-risk status after 12 months of treatment. Results: A total of 83 patients were included in this analysis. Classification of patients according to the tertiles of treprostinil dose achieved at 3 months after drug inclusion shows that after 12 months of follow-up, the median WHO FC in the highest dose group was lower than that in the intermediate dose group (WHO FC II vs. WHO FC III, p = 0.005), the median NTproBNP was lower (922 pg/mL, vs. 1686 pg/mL, p = 0.036) and 6MWD was longer (300 m vs. 510 m, p = 0.015). The French Noninvasive Criteria (NIFC) scale score was higher (2 vs. 0, p = 0.008), and the Reveal scale score was lower (5.0 vs. 8.5, p = 0.034). In the group of patients who exceeded a dose of 19.8 ng/kg/min within 3 months, an improvement in 6MWD was observed significantly more often after one year of therapy, and they were more likely to show an increase in NIFC scale scores after one year of therapy than the group of patients who received the lower dose (65% vs. 30%, p = 0.02). In the group of patients younger than 50 years of age, a statistically significant correlation was observed between the dose of treprostinil achieved after three months of treatment and the parameters assessed after 12 months of treatment, including WHO FC, 6MWD, and NIFC prognostic scale scores (all p < 0.05). Conclusions: The clinical effect of treatment is critically dependent on the rapid escalation of the treprostinil dose during the first three months of treatment.